Circulating Extracellular Vesicles and Their miR “Barcode” Differentiate Alcohol Drinkers With Liver Injury and Those Without Liver Injury in Severe Trauma Patients - Eguchi, Akiko; Franz, Niklas; Kobayashi, Yoshinao; Iwasa, Motoh; Wagner, Nils; Hildebrand, Frank; Takei, Yoshiyuki; Marzi, Ingo; Relja, Borna (Frontiers in Medicine, 2019)
Background: Alcohol abuse is associated with (neuro)protective effects related to (head) injuries, and with negative effects regarding infection rates and survival in severely injured trauma patients (TP). Extracellular vesicles (EVs), which are released during tissue and/or cell injury, can contain a “barcode” including specific microRNAs (miRs) that uncover their origin. We examined whether EVs with a hepatic miR signature can be systemically measured, and whether they can indicate ongoing liver injury in alcohol-intoxicated TP and foretell clinical complications. Patients/Methods: We enrolled 35 TP and measured blood EVs, IL-6, TNF-alpha, IL-1beta, IL-10 and IL-33, alcohol (ethanol, EtOH) concentration (BAC), GLDH, GGT, AST, ALT, leukocytes, platelets and bilirubin. Within circulating EVs we measured the expression levels of miR-122, let7f, miR21, miR29a, miR-155 and miR-146a. Patients of alcohol-drinkers were grouped into “alcohol drinkers with liver injury (LI)” (EtOH with LI) or “alcohol drinkers without LI” (EtOH w/o LI) and compared to “non-drinkers” (no EtOH). We assessed systemic injury characteristics and the outcome of hospitalization with regard to sepsis, septic shock, pneumonia or mortality. Results: EtOH with LI patients had significantly increased rates of pneumonia vs. the EtOH w/o LI group. EVs, IL-6 and IL-33 levels were significantly increased in EtOH with LI vs. EtOH w/o LI group (p<0.05). EV number correlated positively with ALT and IL-6 (p<0.0001). Two miRs, miR-122 and let7f, were increased only in the blood EVs from the EtOH with LI group (p<0.05). Five miRs, miR-122, let7f, miR-21, miR-29a and miR-146a, were reduced in the blood EVs from the EtOH w/o LI group, vs. no EtOH (p<0.05). Notably miR-122 correlated significantly with increased bilirubin levels in the EtOH with LI group (p<0.05). Conclusions: Liver injury in alcohol-intoxicated TP is reflected by increased EV numbers, their specific miR barcode, and the correlated increase of systemic inflammatory markers IL-6 and IL-33, with IL-33 being a marker of alcoholic liver disease. Interestingly, severely injured TP without liver injury were found to have a reduced number of liver-derived EVs, no observed inflammatory infiltration and reduced their specific miR “barcode”.